Adventures of Huckleberry Finn - Twain, Mark, 1835-1910.; Elliott, Emory, 1942- (Oxford : Oxford University Press, 1999)
The story of Huck's escape from his brutal father and the relationship that grows between him and Jim, a slave fleeing an even more brutal oppression, proved enormously influential in the development of American literature.
Includes bibliographical references (p. xlviii-l).
Accelerated Reader/Renaissance Learning
Keywords: Finn, Huckleberry (Fictitious character) -- Fiction; United States -- Social life and customs -- 19th century -- Fiction